Desain Pembelajaran sebagai Upaya Peningkatan Kualitas Pembelajaran al-Quran Hadis - Ashif Az-Zafi; Partono Partono (Matan : Journal of Islam and Muslim Society, 2020)
The writing of this paper tries to study the learning design of the AlQuran Hadis subjects in an effort to boost the quality of learning. Problems in this paper are still teachers who have not been maximized in learning and have not mastered a variety of learning methods and strategies. Therefore, it is necessary to have a description in designing the learning of the Al-Quran Hadis. The method used is descriptive qualitative. The results of this paper are that in designing the learning of the Al-Quran Hadis the methods used by the teacher must be varied and the efforts that must be made by the teacher to improve the quality of learning need to be improved in learning the wrong al-Quran Hadis by using thematic interpretation methods and the teacher must be able to improve his learning strategy and be able to use the media innovative and attractive.